Opioid pharmacovigilance: A clinical-social history of the changes in opioid prescribing for patients with co-occurring chronic non-cancer pain and substance use. (August 2017) - Knight, Kelly R.; Kushel, Margot; Chang, Jamie S.; Zamora, Kara; Ceasar, Rachel; Hurstak, Emily; Miaskowski, Christine
Abstract: There is growing concern among US-based clinicians, patients, policy makers, and in the media about the personal and community health risks associated with opioids. Perceptions about the efficacy and appropriateness of opioids for the management of chronic non-cancer pain (CNCP) have dramatically transformed in recent decades. Yet, there is very little social scientific research identifying the factors that have informed this transformation from the perspectives of prescribing clinicians. As part of an on-going ethnographic study of CNCP management among clinicians and their patients with co-occurring substance use, we interviewed 23 primary care clinicians who practice in safety-net clinical settings. In this paper, we describe the clinical and social influences informing three historic periods: (1) the escalation of opioid prescriptions for CNCP; (2) an interim period in which the efficacy of and risks associated with opioids were re-assessed; and (3) the current period of "opioid pharmacovigilance, " characterized by the increased surveillance of opioid prescriptions. Clinicians reported that interpretations of the evidence-base in favor of and opposing opioid prescribing for CNCP evolved within a larger clinical-social context. Historically, pharmaceutical marketing efforts and clinicians' concerns about racialized healthcare disparities in pain treatment influenced opioid prescription decision-making. Clinicians emphasized how patients' medical complexity (e.g. multiple chronic health conditions) and structural vulnerability (e.g. poverty, community violence) impacted access to opioids within resource-limited healthcare settings. This clinical-social history of opioid prescribing practices helps to elucidate the ongoing challenges of CNCP treatment in the US healthcare safety net and lends needed specificity to the broader, nationwide conversation about opioids. Highlights: Opioid prescribing practices of US primary care clinicians are under-researched. Safety net healthcare settings serve the majority of patients receiving opioids. The evidence-base in favor of and opposing opioid prescribing has evolved. Poverty, race, and limited healthcare resources influence opioid prescribing. This analysis elucidates current consequences of opioid pharmacovigilance.